Answer:
![Equation : \\(x+3)^2 + ( y -2)^2 = 36](https://img.qammunity.org/2022/formulas/mathematics/high-school/2kpqzrweyx6psfayyrkfa8snbe0gju1jue.png)
Explanation:
For standard form the circle's equation we need the centre of the circle and the radius.
Step 1: Find the centre
If the centre is not given find the end points of the diameter
and then find the mid point.
Let the end points of the diameter be : ( - 3 , 8 ) and ( -3 , -4 )
The mid-point of the diameter is :
![Mid-point = ((-3 + - 3)/(2), (-4+8)/(2)) = (-3, 2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/228m1qoj81j2rkh3q0y70zler7687j231u.png)
Therefore, centre of the circle = ( -3 , 2 )
Step 2 : Find radius
![Radius = (Diameter )/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/fzz79qo4eyy2y9t0h0u2vtxqzcc39yzbtw.png)
Diameter is the distance between the end points ( -3 , 8) and ( -3 , -4 )
That is ,
![Diameter = √((-3-(-3))^2 + ( -4 -8)^2)\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/sx4m8r013bdclj0252p1c4qvs0qil06abl.png)
![= √((-3 + 3)^2 + (-12)^2)\\\\=√(0 + 144)\\\\=12](https://img.qammunity.org/2022/formulas/mathematics/high-school/g78xoejdux18qsohyhjonrsco8kbgvk9tz.png)
Therefore ,
![Radius = (12)/(2) = 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/w5isx24k3uioy5f87ccikpwjsox2qe6vx8.png)
Step 3 : Equation of the circle
Standard equation of the circle with centre ( h ,k )
and radius ,r is :
![(x - h)^2+(y -k)^2 = r^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/gw36mnzda30gzgxbalvwj30dusr3q1ibbi.png)
Therefore, the equation of the circle with centre ( -3, 2)
and radius = 6 is :
![(x - (-3))^2 + (y - 2)^2 = 6^2\\\\(x + 3)^2 + (y - 2)^2 = 36](https://img.qammunity.org/2022/formulas/mathematics/high-school/3hnd4baxtgrs412ktgi572wkmm3xinwelr.png)